Acessibilidade de conteúdos televisivos para pessoas com deficiências: limitações e propostas de melhoramento - García-Prieto, Victoria (2022)
Access to information is a fundamental right that becomes relevant in the case of television, especially public television, due to its mission of public service and social inclusion. Guaranteeing access for people with disabilities to audiovisual content is essential to achieve the objectives of quality of life and full equality of opportunities. To this end, international and national legislation establishes that television content must include subtitles, audio descriptions, and sign language. However, the fact that television complies with legal requirements does not necessarily mean that it meets the needs of viewers with disabilities. This qualitative exploratory study in the United Kingdom and Spain analyzes the situation of accessibility in public television through qualitative interviews with thirteen experts from the associative movement, television, and the academy. By confronting their different positions, it shows that the levels and quality of accessibility are lower than desired, which prevents universal access for people with visual, auditory, and audiovisual disabilities. Likewise, from different angles, it proposes improvement alternatives to the main demands of the recipients.